Online Pollen Catalogs Network: Digital database of pollen and spores of current plants and fossils - Da Silva, Cláudia Inês (2020)
The Online Pollen Catalogs Network - RCPol (www.rcpol.org.br) was conceived in 2009, officially created in September 2013, and opened to the scientific community at the XIV International Palynological Congress and X International Organization of Palaeobotanical Conference in Salvador, State of Bahia, Brazil, in 2016. Since its conception, RCPol has been proposed with the main objectives of creating a digital repository of pollen and plant collections for their conservation and avoiding potential loss of material, becoming a free access tool to researchers (collaborators) and the global community